SPIRITUAL AND EDUCATIONAL VIEWS IN THE WORKS OF THE PRESIDENT - Madumarov Talantbek Tolibjonovich (Galaxy International Interdisciplinary Research Journal, 2021)
Ask spirituality in a word, this is the face of every state. because if you go to a developed state where you want, then in someplace it is assessed depending on the spirituality and culture of the people about what kind of state it is. And spirituality can be determined by the origin of the religion and language of each state. In this regard, the distinguished president of our country is speaking in every report, Apart from him, a mature scientist will take an example from our grandparents. In the work of his new Uzbekistan strategy, he also introduced a chapter on spirituality as a separate topic. In it, the introductory word began with the following words. “ In my opinion, there is a great illumination of the world of mankind –the flash of spirituality.